Konsumsi Berita Insidental di Media Sosial pada Generasi Dewasa - Era Realita; Usman Setiadi (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2022)
Incidental news is the result of an algorithm system implemented by media companies. This study shows how background of the social media users influence incidental news consumtion. The method used is literatures review and short interviews with 20 adults working in various sectors with an age range of 23-25 years. The results show that background of profession and age are influencing the choose of news content. Responding to the emergence of incidental news, several respondents did not care about the origin of the news. As long as the content loaded interests them, there is nothing to question. they also think that incidental news can be an effective shortcut to reach the original source of the news. It can be concluded that adults generally feel helped in the news search process with incidental news. Nevertheless, in consuming incidental news, we should remain vigilant and careful because not all news sources are accurate and from the theory of incidental news emergence that utilizes digital track records that can threaten our personal data.